OGOH-OGOH : AN INDONESIAN CREATIVE LOCAL WISDOM INSPIRED BY HINDU PHILOSOPHY AS ETHNO-PHYSICS - Saphira, Hanandita Veda; Admoko, Setyo; Suprapto, Nadi (UHN I Gusti Bagus Sugriwa Denpasar, 2022)
One of the local wisdom that can be used for physics learning-media is Ogoh-Ogoh. Previous research, exploration of the value of Physics is limited to others local wisdom. Thus, the authors realized the need for further identification of ogoh-ogoh as the local culture of Hindus who are in Surabaya as a research topic, which aims to develop the learning-media of physics integrated local-wisdom in schools or people and analyze ethnoscience conception on Ogoh-Ogoh. This research is included the type of qualitative research using triangulation: interviews, indirect observations and literacy studies. Based on the results of analysis and discussion related to the concept of Physics in ogoh-ogoh culture, it can be known there is an application of physics concepts that are not realized by the perpetrators of Ogoh-Ogoh. Thus, a local wisdom Ogoh-Ogoh can be used as a medium of learning, especially in the field of Physics, one of which is to increase their science-Physics (Ethno-Physics) knowledge into more real scientific knowledge.